Invective Vocabulary in Media Discourse at the Beginning of the 21st Century: A Psycholinguistic Aspect - Oleksandr Mezhov; Maryna Navalna; Nataliia Kostusiak (East European Journal of Psycholinguistics, 2020)
The article draws on a broad interpretation of the invective as a non‑standard (non-literary) vocabulary known in linguistics as jargonisms, expletives, vulgarisms; foul, pejorative, negatively coloured, disparaging, slang, obscene, coarse, abusive, taboo words and other lexical units that contain the meaning of an insult in their semic structure; less often the invective is understood as a codified (literary) vocabulary which acquires the insulting meaning in a context as an expression of the speaker’s communicative intention and pragmatic tactics of consciously offering a public affront to a specific addressee of communication. The aim of the research is the lexico-semantic and communicative-pragmatic characteristics of the invective vocabulary in a modern media discourse and social networks as a specific verbal means of a psychological impact on the consciousness of the recipients. By resorting to the method of free word association test, the authors have studied a conscious and/or subconscious reaction of Ukrainian females and males to pejorative by-words that stir up a feeling of insult. 100 people have been selected as respondents (50 people of each gender). All of them were Ukrainian native speakers including female and male lecturers and students of Lesya Ukrainka Eastern European National University (Ukraine) and Pereiaslav-Khmelnytskyi Hryhorii Skovoroda State Pedagogical University (Ukraine); choosing the stimuli, the authors proceeded from the frequency of their use in the texts of modern mass media (out of 300 detected nominations the authors used 100 units). According to the extent of the insult caused by the given words they were rated on a scale of 1 to 4 which made it possible to combine the analyzed stimuli into four groups with the following scores: 1) 2.65–2.93; 2) 1.67–2.31; 3) 1.03–1.54; 4) 0 (zero). The experiment gave a clear structure of the invective – a psycholinguistic category including a communicative-pragmatic intention of the insult